Torque control of a 5 KW, 220 V separately excited DC motor using microcomputer - Mohamed Mostafa Ramadan Ahmed; Atef A. Elemary; Zuhair Muhammed Alaas; Abdallah Mohamed Hamada (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Fast torque control is crucial for various applications, including diesel-electric locomotives, electric automobiles, and steel plants. The purpose of this paper is to utilize a microcomputer to control the torque of a separately-excited DC motor fed from a single-phase semi-controlled converter. There are numerous strategies to determine torque using direct or indirect methods. The greatest issue of direct strategy using torque meters is that the measuring device must be installed between the motor and the load. In this paper, we avoid this challenge by employing the indirect approach, specifically by monitoring several DC machine-specific quantities such as voltage, current, and speed, which are easier to determine experimentally. This technology is unquestionably helpful in real-world applications since it eliminates any mechanical impact on the installation. This paper describes the system configuration and provides an explanation of the architecture and system features. The simulation of the proposed system using TUSTSIM dynamic simulation program which is capable of simulating the control system with a digital controller in the loop is presented. An implementation of microcomputer-assisted torque control of DC separately excited motor with proportional integral (PI) controllers is presented. A typical oscillography of the driving characteristics is provided along with the experimental results.